CLOUD COMPUTING SEBAGAI MEDIASI PENGARUH DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA ORGANISASI : CLOUD COMPUTING AS A MEDIATION OF THE INFLUENCE OF TOP MANAGEMENT SUPPORT ON ORGANIZATIONAL PERFORMANCE - Syafitri, Lidya; Fitrios, Ruhul; Indrawati, Novita (Universitas Riau, 2024)
The purpose of this study was to analyze the effect of top management support on organizational performance with cloud computing as a mediator so as to improve the performance of MSMEs to be more aware of the use of accounting information systems, especially the maximum use of cloud computing. This research was conducted at MSMEs registered at the Pekanbaru City Cooperative and MSME Office. With a total sample in this study of 189 MSMEs selected from a population of 13,540 MSMEs registered at the Pekanbaru Cooperative Office using a survey method, sampling using the Hair formula and questionnaires distributed to MSME executives/owners both offline and online. The sampling technique used convenience sampling technique. Furthermore, the data analysis technique uses the SmartPLS 3 application. The results showed that (1) Top management support affects organizational performance, (2) Cloud computing affects organizational performance, (3) Top management support affects cloud computing, (4) Cloud computing mediates top management support on organizational performance.